Optimal monitoring point for temperature and power control in microwave ablation system by using FEM - S. Pairoch (2018)
This study presents an optimal location of monitoring point for using by PID system to control temperature and output power of hepatic cancer microwave ablation system. We investigated a relation between output power and treatment time in hepatic ablation. A simple simulation model was adapted from COMSOL FEM solver. As a preliminary, monitoring point was supposed to place at 0.5 centimeter besides ablation probe. The simulation results shown that temperature at this monitoring point is linearly related to output power and treatment time. ©2012 IEEE.